Unimodality of certain sequences connected with binomial coefficients - Belbachir H (JOURNAL OF INTEGER SEQUENCES - ONLINE, 2007)
This paper is devoted to the study of certain unimodal sequences related to binomial coefficients. Although the paramount purpose is to prove unimodality, in a few cases we even determine the maxima of the sequences. Our new results generalize some earlier theorems on unimodality. The proof techniques are quite varied.